Efektivitas Penerimaan Pesan Dakwah Konvensional Dan Dakwah Online Jamaah Teras Dakwah - Wahyu Nisa (Hikmah, 2023)
A da'wah activity can be said to be successful if religious messages are conveyed properly so as to change the mindset and habits of the congregation in a better direction. Usually da'wah is carried out on the pulpit with the lecture method, through someone's actions, and through writing that is easily accessible, such as in newspapers and articles. However, in the current digital era, people are required to adapt and keep abreast of technological developments. The presence of the internet, with its characters that can be accessed anytime and anywhere, allows the development of online da'wah activities. Online preaching makes it easier for mad'u because they don't have to be present face-to-face with preachers to study religion. However, the freedom of internet access is often misused; the entire da'wah video is cut into short videos, which often cause misunderstandings that affect the reception of messages by mad'u. This study aims to: (1) find out the comparison of the effectiveness of conventional da'wah and online da'wah at Teras Da'wah; (2) Knowing whether there is an effect of effectiveness on conventional preaching and online preaching on Teras Dakwah. This study used a descriptive-quantitative approach with the type of comparative research The pretest-posttest control group design used questionnaires and interviews. Based on the results of the independent tests, the sample t-test has a sig. (two-tailed) value of 0.0000.05. So it can be concluded that online da'wah is more effective than conventional da'wah for the Teras Dakwah congregation. Keywords: Effectiveness, online da'wah, conventional da'wah